Analysis of The Impact of Placements In Bi, Securities, and Loans Disbursed on Net Income of Banks Listed on The Indonesia Stock Exchange - Maya Macia Sari; Aulia Aulia; Fara Dhia Naaura (Jurnal Akuntansi, 2024)
This study aims to test and find out more clearly how “Analysis of the Effect of Placement on Bi, Securities and Disbursed Loans on Net Income at Banks Listed on the Indonesia Stock Exchange”. This study uses quantitative methods involving 19 companies with an observation period of 2020-2023. Based on the partial research results, it is concluded that the BI Placement variable has a partially positive and significant effect on Net Income. Securities have no significant effect on Net Income. Disbursed Loans has a positive and significant effect on Net Income. While simultaneously Placement of BI, Securities and Loans have a significant effect on Net Income. The contribution of influence amounted to 88.8%.  The results are in line with the principles of Stewardship Theory. Bank managers who act as good stewards will manage assets prudentially, comply with regulations, consider risk and return aspects, and prioritize the long-term growth and success of the company.